Senam Peregangan SEHATI (Senam Sehat Kelompok Wanita Tani) untuk Menurunkan Keluhan Muskuloskeletal - Sumardiyono Sumardiyono; Ratna Fajariani; Haris Setyawan; Rachmawati Prihantina Fauzi; Maria Paskanita Widjanarti; Rachel Alma Syevina Putri; Auraningtyas Kurnia Ratri; Fitriyani Nurjanah; Ila Fitriani; Muiz Mahardika; Nabila Dean Pradetha; Naufal Tio Widjanarko; Pambayun Khairul Rijal Muzakki; Rofi Shiddieq Putranto; Syifa Azzahra (Universitas Muhammadiyah Surakarta, 2024)
Farmers are prone to musculoskeletal complaints due to heavy physical activities, non-ergonomic postures, and insufficient rest. These complaints can lead to decreased productivity and reduced quality of life and become an economic burden for farmers. This community service program aimed to develop and implement the SEHATI (Healthy exercise for women farmers group) stretching exercise correctly to reduce musculoskeletal complaints in farmers. The program was conducted on November 20, 2023, and was attended by 21 women's farmer group members. The program consisted of situation analysis, implementation, monitoring, and evaluation. The results of the SEHATI exercise showed a decrease in musculoskeletal complaints in the neck, shoulders, arms, hands, waist, and legs between before and after the exercise, with an average score of 30.2 points to 26.5 points (a decrease of 3.7 points). The paired t-test showed a p-value of 0.001 (p < 0.05), indicating a significant difference. In conclusion, the SEHATI exercise was effective in reducing musculoskeletal complaints. Recommendations include socializing and training the SEHATI exercise to other women's farmer groups, conducting further evaluations of the long-term effectiveness of the SEHATI exercise, and developing training modules for health cadres in Karanganyar Regency.